2016
DOI: 10.1089/thy.2016.0082
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Thyrotropin Improves Endothelial Coronary Flow Reserve in Thyroidectomized Patients with Differentiated Thyroid Cancer

Abstract: rhTSH administration may improve the CFR after the non-pharmacological stressor CPT in DTC patients. The increase of coronary blood flow after rhTSH suggests that TSH may exert a protective effect on the coronary endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The functional meaning of TSH outside the thyroid gland is not fully determined. It has been suggested that TSH may act as a modulator, operating at multiple different systems and organs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Under clinical conditions similar to the ones applied in our study, rhTSH was shown to influence serum ghrelin levels (19), as well as serum levels of total cholesterol and triglycerides without any significant changes of high and low lipoproteins (20).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The functional meaning of TSH outside the thyroid gland is not fully determined. It has been suggested that TSH may act as a modulator, operating at multiple different systems and organs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Under clinical conditions similar to the ones applied in our study, rhTSH was shown to influence serum ghrelin levels (19), as well as serum levels of total cholesterol and triglycerides without any significant changes of high and low lipoproteins (20).…”
Section: Discussionsupporting
confidence: 55%
“…What is more, rhTSH administration was associated with significant deterioration of renal perfusion and reduction in glomerular filtration (23). On the other hand, the protective effect of rhTSH on the coronary endothelium, resulting in an increase of coronary blood flow was observed in a small group of athyroid patients undergoing echo-Doppler examination with evaluation of the coronary flow reserve (24). The effects exerted by TSH on immune cells are not sufficiently described, and the available data were obtained mainly with the use of animal models or in in vitro assays with human PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we successfully used this tool to evaluate coronary endothelial function in patients with Kawasaki disease [ 20 ] and in those with mild thyroid hormone deficiency [ 21 ], two diseases in which the endothelial damage is overt. Of interest, in a subsequent study we observed that recombinant human thyrotropin administration improves CPT derived CFR in differentiated thyroid cancer patients [ 22 ], highlighting therefore the ability of this test in evaluating of pharmacologic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…CPT was performed by placing the subject’s hand and distal part of the forearm in an ice water slurry for 4 min [ 18 , 19 ]. Coronary flow was visualized in the distal left anterior descending coronary artery by transthoracic Doppler echocardiography with a 5 MHz shallow-focus phased-array transducer in the low parasternal long-axis cross section under the guidance of color Doppler flow mapping, according to a standardized protocol of our echo laboratory [ 20 22 ]. Doppler sample volume was placed on the color signal of the left anterior descending artery, and the characteristic biphasic flow pattern with a larger diastolic and a smaller systolic component was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…54 Equally important, a study led by Bernadette Biondi has shown that recombinant human T4 improves endothelial coronary flow reserve in thyroidectomized patients. 55 58 Both THRα and THRβ are found in the kidney. 39,60 Thyroid hormones play paramount roles in the regulation of tubular function.…”
Section: Effects On the Endotheliummentioning
confidence: 99%